Learning models innovation in industrial revolution 4.0 era - Metsa Fajrianti Kusumah Suwandi; Muhammad Alfat (Universitas Pendidikan Indonesia, 2022)
The era of the Industrial Revolution 4.0 has created a shift in every dimension of life, one of which is the education dimension. In anticipating the rapid transformation that is taking place, education must always develop its competence and academic innovation. This study aims to analyze the education that occurs, the learning models used, as well as the innovative curriculum set in the era of the Industrial Revolution 4.0. The method used in this research is the literature study method. The data generated using this method were re-analyzed through the stages of reading and recording data as research material to processing the research materials. The study results show that the Industrial Revolution 4.0 era resulted in changes in human life patterns due to the influence of technological devices. This change underlies the design and establishment of a new innovative curriculum that is in accordance with the 4.0 revolution era. The 2013 curriculum as a complement to the previous curriculum is here to make education accustomed to the use of technological devices. Education as a place to educate the nation's successors needs to keep up with all the changes that occur so that learning can be obtained by students who are not left behind from the latest information. Abstrak Era Revolusi Industri 4.0 telah menciptakan pergeseran pada tiap dimensi kehidupan, salah satunya adalah dimensi pendidikan. Dalam mengantisipasi cepatnya transformasi yang terjadi, pendidikan harus selalu dikembangkan kompetensi serta inovasi akademisnya. Penelitian ini bertujuan untuk menganalisis pendidikan yang terjadi, model pembelajaran yang digunakan, serta kurikulum inovatif yang diterapkan di era revolusi industri 4.0. Metode yang digunakan dalam penelitian ini adalah metode studi pustaka. Data yang dihasilkan menggunakan metode tersebut, dianalisis kembali melalui tahapan membaca serta mencatat data sebagai bahan penelitian hingga mengolah bahanbahan penelitian tersebut. Hasil penelitian menunjukkan bahwa era revolusi industri 4.0 berakibat pada perubahan pola hidup manusia dikarenakan pengaruh perangkat teknologi. Perubahan inilah yang mendasari perancangan dan penetapan kurikulum inovatif baru yang sesuai dengan era revolusi 4.0. Kurikulum 2013 sebagai penyempurnaan kurikulum sebelumnya hadir untuk membuat pendidikan yang terbiasa dengan penggunaan perangkat teknologi. Pendidikan sebagai tempat mendidik penerus bangsa perlu mengikuti segala perubahan yang terjadi supaya pembelajaran yang didapat peserta didik tidak ketinggalan dari informasi terbaru. Kata Kunci: Kurikulum; model pembelajaran inovatif; Revolusi Industri 4.0